2020
DOI: 10.1097/grf.0000000000000595
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic Ovarian Syndrome and Fertility

Abstract: Polycystic ovary syndrome (PCOS) is a common endocrinopathy that has been associated with impaired fertility. This chapter reviews the underlying pathophysiology of PCOS and the associated fertility barriers of the condition. Psychologic concerns, hypothalamic-pituitary, ovarian, and mitochondria dysfunction, obesity, and the role of vitamin D in PCOS are considered with respect to fertility. Lastly, pregnancy risk factors associated with PCOS are also reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…In our research, the number of ovarian follicles was significantly increased (p<0.05) to 18.78+1.20 (Mean+SD) in the PCOS patients. Our findings were in close liaison with Lentscher et al [13]. The results of our study were also supported by a study in which ≥12 follicles on the ovaries were found [6].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our research, the number of ovarian follicles was significantly increased (p<0.05) to 18.78+1.20 (Mean+SD) in the PCOS patients. Our findings were in close liaison with Lentscher et al [13]. The results of our study were also supported by a study in which ≥12 follicles on the ovaries were found [6].…”
Section: Discussionsupporting
confidence: 92%
“…The highest incidence was found by Zandi et al who found a 60.2% incidence of PCOS by NIH criteria [12]. Spontaneous abortions and miscarriages were also caused by PCOS [13]. A study in Nigeria reported a 55.2% incidence of PCOS in infertile women [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…According to the American Society of Reproductive Medicine (ASRM), 70-80% of women with PCOS are infertile. In addition, the Centers for Disease Control and Prevention (CDC) state that PCOS is the most frequent cause of infertility [17]. Drugs like clomiphene citrate and letrozole are usually employed for the induction of ovulation in women with PCOS undergoing fertility treatment [18].…”
Section: Introductionmentioning
confidence: 99%
“…Polycystic ovary syndrome (PCOS) is the most common diagnosed endocrine disorder in women [ 1 ] and a major cause of anovulatory infertility. The prevalence is thought to range from 4% to 26% depending on the population studied [ 2 , 3 , 4 ]. PCOS patients can present a wide range of signs and symptoms, making it difficult to agree on the precise definition of the condition.…”
Section: Introductionmentioning
confidence: 99%